Effectiveness of Conciliation Mediation in Regional Arbitration Branch – National Capital Region - Rebayla, Ethel Jhoann T.; Segre, Joan M.; Rojas, Maria Antoniette V.; Indita, Waliza (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to determine the Effectiveness of Conciliation Mediation in Regional Arbitration Branch – National Capital Region. It employed the descriptive-quantitative method of research using the researchers-made instrument to gather data from the 60 employees of the National Labor Relations Commission. They served as respondents to the study. The researcher personally distributed the tool using the random sampling technique because the researchers distributed the questionnaire to every member of the population and gave them an equal chance of being selected. It was discovered that most respondents were in the age range of 51-60 years old and above, female, married, and 26 years and above in the government service. When the effectiveness of the conciliation medication was tested, the result yielded that the Conciliation Mediation Process, Duration of the Process, Conciliator Mediator Skills, and Termination of the Conciliation Mediation Process in terms of efficacy, efficiency, and reliability were highly effective. Taking into account the result of the study, it was recommended that regular training for conciliators mediators should be conducted so that their skills in settling preliminary labor disputes may be enhanced and which will result in more future settlements between the parties involved. It is also recommended that the conciliator mediators increase their commitment to accommodate all requests and possible assistance to our laborers. It is likewise prudent to train new and incoming conciliator mediators so that as early as now, they will be given a chance to experience and explore handling conciliation mediation.